Building Repurchase Intention of Customers for Grab Transportation Services in Brosem Smes, Batu City With Customer Satisfaction as a Mediator Variable - Lestari, Yogi Dwi; Sudarmiatin; Wardana, Ludi Wishnu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to determine effectiveness customer satisfaction in mediating service quality and customer value in building repurchase intention Grab transportation service for Brosem SMEs, Batu City. This research is quantitative descriptive. The population of this research is members of Brosem SMEs Kota Batu who use Grab transportation services with a sample of 76 respondents. Sample size guidelines using saturated samples. Data analysis in this research used descriptive statistical techniques and inferential statistical analysis with the SPSS application. The results of this research show that service quality proven to have no effect on customer satisfaction but it has been proven to have an effect on repurchase intention, either directly or through mediation customer satisfaction. Where as customer value proven to have a positive and significant effect on customer satisfaction and its influence on repurchase intention with mediation customer satisfaction. However customer value has no effect on repurchase intention directly.